Islamic Education In The Merdeka Belajar Curriculum - Yuli Supriani; Asep Supriyadi; Bambang Samsul Arifin; Uus Ruswandi (Edumaspul: Jurnal Pendidikan, 2022)
This study aims to determine Islamic religious education in the independent learning curriculum. The method used in this study uses a library method or approach, that literature or literature study can be interpreted as a series of activities related to methods of collecting library data, reading and recording and processing research materials. The results of this study indicate that the concept of "Merdeka Belajar" is an effort to realize freedom of thought. The existence of this policy provides great hope for educational institutions to explore and develop the quality of education in their institutions. Islamic Religious Education as a series of Islamic subjects is delivered both formally in schools as well as informally and formally in homes and communities with material being taught starting from the elementary school level to tertiary institutions must respond to this "Merdeka Belajar" policy by training students under the supervision of Education teachers Islam is to always think critically so that students are expected to have more mature, wiser, more careful and noble morals in practicing the teachings of Islam itself.